PENDAYAGUNAAN ZAKAT Studi Implikasi Hukum Ekonomi Islam Terhadap Pendayagunaan Zakat di Lembaga/ Badan Amil Zakat (BAZ) Kota Dumai - susiana, susiana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Islam Indragiri, 2015)
This studi aims to examine in depth and critically examine how the implementation of zakat. Can be useful to overcome the problem of community in Dumai through the economic empowerment of the poor. Rationale for doing research with the theme of charity is based on the utilization of an understanding of the position of zakat which has very important issues related to economic, social an religious. From the economic aspect, zakat has a very high economic potential if managed optimally. In terms of religiuos, zakat is also able to reinforce faith and devotion ti God almighty.